Refleksi Gelombang Pada Pemecah Gelombang Tipe OWC (Oscillating Water Column) - Sugianto Sugianto; Rita Tahir Lopa; Riswal Karamma; Chairul Paotonan (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
Breakwater functions as a coastal protection structure, it is important to design a breakwater model that is able to perform a dual function as a wave energy catcher. To gain a deeper understanding of the wave reflection influenced by the slope and inlet hole on the OWC type breakwater model, a more comprehensive study is needed. This study aims to determine the reflection of waves in front of the OWC type breakwater model with variations in slope angle and variations in inlet openings. The research method is experimental. The study used an OWC type wave absorber model with two variations of tilt angle (q) 450 and 600, variation of stroke with flap movement of 4, 5, and 6, variation of water depth (d) 17.5 cm, 21 cm, and 24.5 cm and variation of openings (closed inlet, open inlet 5 cm, 10 cm, and 15 cm). The results showed that the effect of the inlet opening (h) on the Kr value is quite significant, indicated by the reflected waves being large. The Kr value is greater with increasing inlet openings, due to the relatively small damped waves and the pressure that occurs from inside the inlet hole is greater, the Kr value is large in the OWC type breakwater model.